OCCURRENCE OF THROMBOTIC MICROANGIOPATHY IN A PATIENT WITH GRANULOMATOSIS WITH POLYANGIITIS AFTER REMISSION INDUCTION THERAPY: A RARE PRESENTATION - Ege Sinan Torun; Betül Köstek; Çağlar Çakır; Gülay Koçak (İstanbul Tıp Fakültesi Dergisi)
In the literature thrombotic microangiopathy (TMA) associated with ANCA-associated vasculitis (AAV) has only been reported in isolated case reports. Here, we report a patient with granulomatosis with polyangiitis (GPA), who presented with TMA after initiation of remission induction therapy. A 36-yearold male patient presented with dyspnea and decreased urine output. Laboratory results demonstrated elevated creatinine, low albumin, low hemoglobin, normal leukocyte and platelet count, normal LDH, and elevated acute phase reactants. Urinalysis revealed proteinuria (1275 mg/day) and an active urine sediment. Serum complement levels were normal and proteinase 3 ANCA titer was> 200 IU/ml. Urinary ultrasound revealed normal kidney sizes and normal parenchymal thicknesses with increased renal parenchymal echogenicity. A kidney biopsy revealed pauciimmune crescentic glomerulonephritis. The diagnosis was GPA and an induction treatment of pulse steroid, intravenous cyclophosphamide, and plasma exchange was initiated. After two doses of cyclophosphamide, rituximab treatment was initiated. Fifteen days after the second dose of rituximab, thrombotic microangiopathy (TMA) was considered in the patient who had no increase in hemoglobin value (despite initiation of erythropoetin) and decreased platelet count. Peripheral blood smear revealed 5-9 schistocytes in each area. A corrected reticulocyte count was elevated, and haptoglobin was low. ADAMTS13 activity was normal. Plasma exchange was not reinitiated. The kidney biopsy was re-evaluated, but no histopathological changes consistent with TMA were found. The patient was under follow-up for TMA by checking his hematological parameters once a week. Two months later, at the third month of rituximab treatment, an increase in hemoglobin and platelet values was observed. Reticulocyte percent and haptoglobin were within normal limits. His follow-up as an outpatient is continuing. In most of the reported cases of TMA associated with ANCA-associated vasculitis, TMA appeared in the course of active vasculitis. Our case is noteworthy due to the fact that TMA developed after the active phase of GPA, even after the initiation of potent remission induction therapy